IN VITRO ANTI-ARTHRITIC ACTIVITY OF CISSUS QUADRANGULARIS STEM EXTRACT - P, Vaijayanthimala; M, Sakthipriya; B, Sangameswaran (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present investigation deals with the study of in vitro anti-arthritic activity by inhibition of protein denaturation method by bovine serum albumin method and egg albumin method. Cissus quadrangularis Linn plant is a perennial tendril climber with quadrangular stem. It is used in the treatment of gout, syphilis, stomach ache, regularized the menstrual cycle, antimicrobial activity, and piles in Ayurvedic medicine, and traditionally used for the bone fracture. Method: The air-dried powder of C. quadrangularis Linn (stem parts) was extracted using a Soxhlet apparatus with methanol C. quadrangularis (MECQ) and aqueous C. quadrangularis water (AECQ) as solvent. The extracts were concentrated under reduced pressure. The activities were carried out using the following concentration (100, 200, 300, 400, and 500 Î¼g/ml) and compared with diclofenac as standard drug. It has significant in vitro anti-arthritic in both the methods. Result: The extract of C. quadrangularis possessed significant anti-arthritic property in MECQ than compared to AECQ. Conclusion: Activity may be due to the presence of the chemical profile such as phenolic acid, flavonoid (leuteotin), and Î²-sitosterol. The results of the study have suggested in the use of C. quadrangularis Linn as a potent anti-arthritic in several applications.